Golden orb-weaving spider (Trichonephila clavipes) silk genes with sex-biased expression and atypical architectures. Issue 1 (22nd December 2020) - Correa-Garhwal, Sandra M; Babb, Paul L; Voight, Benjamin F; Hayashi, Cheryl Y
Abstract: Spider silks are renowned for their high-performance mechanical properties. Contributing to these properties are proteins encoded by the spidroin (spider fibroin) gene family. Spidroins have been discovered mostly through cDNA studies of females based on the presence of conserved terminal regions and a repetitive central region. Recently, genome sequencing of the golden orb-web weaver, Trichonephila clavipes, provided a complete picture of spidroin diversity. Here, we refine the annotation of T. clavipes spidroin genes including the reclassification of some as non-spidroins. We rename these non-spidroins as spidroin-like (SpL) genes because they have repetitive sequences and amino acid compositions like spidroins, but entirely lack the archetypal terminal domains of spidroins. Insight into the function of these spidroin and SpL genes was then examined through tissue- and sex-specific gene expression studies. Using qPCR, we show that some silk genes are upregulated in male silk glands compared to females, despite males producing less silk in general. We also find that an enigmatic spidroin that lacks a spidroin C-terminal domain is highly expressed in silk glands, suggesting that spidroins could assemble into fibers without a canonical terminal region. Further, we show that two SpL genes are expressed in silk glands, with one gene highly evolutionarily conserved across species, providing evidence that particular SpL genes are important to silk production. Together, these findings challenge long-standing paradigms regarding the evolutionary and functional significance of the proteins and conserved motifs essential for producing spider silks.